EXPLORING THE USE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZED LEARNING ENVIRONMENTS IN THE TRAINING OF SPECIALISTS IN THE FIELD OF MANAGEMENT OF EDUCATIONAL INSTITUTIONS (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.